Collaborative Governance Dalam Upaya Peningkatan Indeks Mutu Pendidikan di Jawa Barat Melalui Program Sekolah Gratis - Nabilla Septiani Herawan; Sintia Dwia Putri; Syilvia Julianti; Andre Ariesmansyah (Jurnal Ilmiah Wahana Pendidikan, 2023)
The free school program is one of the policies issued by the Central Government which aims to help students who are unable to continue their studies and improve the quality of education index in West Java. This study aims to analyze the success of the program, the research method used is qualitative descriptive, with data collection techniques through interviews and literature studies. Based on the research results, the province of West Java experienced an average increase in the school duration index (RSL) compared to the previous year, which means that this free school program has been successfully implemented.